Extrahepatic cytochrome P450s play an insignificant role in triptolide-induced toxicity - Yuan Wei; Dujun Wang; Meng Chen; Zhen Ouyang; Shuo Wang; Jun Gu (BMC, 2018)
Abstract Background Triptolide, an active ingredient of Chinese medicine plant Tripterygium wilfordii Hook.f., has been shown to exert anti-tumor, immunosuppressive, anti-inflammatory, and anti-fertility pharmacological effects. However, triptolide also causes severe side effects, which are manifested as toxicities in multiple organs. The aim of this study was to analyze the role of extrahepatic cytochrome P450 enzymes in triptolide-induced toxicity. Methods Xh-CL mouse model with normal liver, but low extrahepatic P450 expression levels was used in this study. Xh-CL mice and C57BL/6 (wildtype, WT) mice were treated with 200 μg/kg triptolide intraperitoneally every other day for 30 days. The serum levels of alanine aminotransferase (ALT), aspartate transaminase (AST), creatine (Cre), and blood urea nitrogen (BUN) were detected by kits. The changes of tissue were observed with H&E staining. Two groups of mice (Xh-CL and WT animals), were received a single dose of 1 mg/kg TP by oral gavage for pharmacokinetic analysis. Results Xh-CL mice displayed higher serum levels of ALT, AST, Cre, and BUN compared to untreated Xh-CL mice. The organ-to-body weight ratio for spleen was high, while that for testes was low. Histopathological changes were observed in multiple organs. However, compared with triptolide-treated WT mice, no significant differences in either blood chemistry or histopathology were recorded. Furthermore, pharmacokinetic studies showed no significant differences between triptolide-treated Xh-CL and WT mice. Conclusions Our findings suggest that sub-chronic triptolide treatment can induce toxicities in mouse kidney, spleen, and testis with or without normal local P450 functions. Therefore, extrahepatic P450s play an insignificant role in triptolide-induced toxicity.